Dual‐side nanostructured surface for enhancement of broadband light transmission. (1st August 2013) - Park, Yong Min; Kim, Byeong Hee; Seo, Young Ho
Abstract : Presented is a surface nanostructuring technology for enhancing the broadband light transmittance of polymethyl methacrylate sheets. Single‐side and dual‐side nanostructured sheets were fabricated by a hot embossing process using nanoporous alumina moulds. The fabricated nanostructured surfaces showed appreciable broadband light transmission characteristics because of the size distribution of their nanostructures. Single‐side and dual‐side nanostructured sheets showed a maximum light transmittance of 96.11 and 98.74%, respectively, whereas a pristine sheet showed a light transmittance of 93.54%.